2010
DOI: 10.4028/www.scientific.net/amm.24-25.393
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Buckling Analysis of Delaminated Hybrid Composite Beam Structures

Abstract: Abstract. In this paper the effect of delamination position on the critical buckling load and buckling mode of hybrid composite beams is investigated. Experimental and numerical studies are carried out to determine the buckling load of delaminated composite beams. The laminated composite beams with various laminate designs of [G 90 4 were manufactured and tested to find the critical buckling load. Three different defect positions were placed through the thickness to find three main buckling modes. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Esfahani et al. [13] used numerical simulation to study the effect of the through-thickness position of an initial delamination in laminated composite beams. They concluded that a delamination located closer to the surface resulted in a lower buckling capacity of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Esfahani et al. [13] used numerical simulation to study the effect of the through-thickness position of an initial delamination in laminated composite beams. They concluded that a delamination located closer to the surface resulted in a lower buckling capacity of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Obdrzalek and Vrbka (2010) examined the buckling behavior of a small delaminated plate subjected to compression loading by means of FE analysis. Esfahani et al (2010) made experimental and numerical analysis of delaminated hybrid composite beam structures. Mohsen and Shokohi (2010) studied numerically the buckling and post buckling analysis of composite laminated structures having delaminations by using the generalized differential quadrature method.…”
Section: Introductionmentioning
confidence: 99%
“…Delamination can be initiated in FRP due to even a low-energy impact (i.e., caused by the impact of a falling tool during fabrication) and/or other manufacturing induced flaws. Esfahani et al [59] carried out a numerical study and showed that the presence of a delamination had a negative impact on the buckling capacity of their specimens, especially when the delamination was close to the specimen’s outer laminae. Kim and Hong [60] reported that the length and position of the delamination were two parameters that had a large influence on the buckling mode and post-buckling behaviour of laminated composites.…”
Section: Introductionmentioning
confidence: 99%